2001
DOI: 10.1097/00007691-200112000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cyclosporine Withdrawal on Mycophenolic Acid Pharmacokinetics in Kidney Transplant Recipients With Deteriorating Renal Function: Preliminary Report

Abstract: Mycophenolic acid (MPA) concentrations are lower in transplant recipients receiving mycophenolate mofetil (MMF) and cyclosporine compared with MMF with tacrolimus. It is not clear whether this is due to an effect of cyclosporin or tacrolimus on MPA pharmacokinetics. To study this effect, kidney transplant recipients with deteriorating renal function (n = 5) receiving cyclosporin and steroids were given mycophenolate mofetil over 4 weeks during a run-in phase (1 g/d in week 1, 1.5 g/d in week 2, 2 g/d starting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
58
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 15 publications
0
58
0
Order By: Relevance
“…25,26) In addition, we showed that the MPAG/MPA ratio in CNI(Ϫ) patients was not higher than the median ratio in patients treated with TAC. It has been reported that CyA interferes with the enterohepatic circulation of MPAG, and that TAC may interfere with the activity of UGT.…”
Section: Discussionmentioning
confidence: 75%
“…25,26) In addition, we showed that the MPAG/MPA ratio in CNI(Ϫ) patients was not higher than the median ratio in patients treated with TAC. It has been reported that CyA interferes with the enterohepatic circulation of MPAG, and that TAC may interfere with the activity of UGT.…”
Section: Discussionmentioning
confidence: 75%
“…Of particular relevance is the impact of CNIs, including CsA and tacrolimus, on MPA exposure. In general, renal allograft recipients receiving MMF in combination with CsA have lower MPA plasma concentrations per unit dose of MMF than patients not receiving CsA (27), and MPA plasma concentrations have been shown to rise significantly following CsA discontinuation (28,29). CsA decreases biliary excretion of MPAG (30,31) by a mechanism that involves inhibition of multidrug resistance-associated protein 2, a multispecific organic anion transporter present in the bile canalicular membrane of hepatocytes (32)(33)(34)(35).…”
Section: Interactions Between Mmf and Other Immunosuppressive Agentsmentioning
confidence: 99%
“…Further studies to define the nature of this interaction have included a control group receiving MMF alone, without addition of a calcineurin inhibitor (80)(81)(82). A small study (80) compared the mean MPA predose concentrations (measured by EMIT) of 11 renal transplant patients receiving MMF and prednisone with those of 18 patients receiving MMF, CsA, and prednisone.…”
Section: Does the Drug Have A Narrow Therapeutic Range For The Specifmentioning
confidence: 99%